Faktor-Faktor yang Mempengaruhi Akuntabilitas Kinerja Instansi Pemerintah Daerah - Marsya, Anisa Lutvia; Ferawati, Indah Wahyu; Wicaksono, Bambang (Akuisisi : Jurnal Akuntansi, 2025)
The purpose of this research is to find out how the implementation of local government accounting systems, reporting systems, and compliance with statutory regulations influence the accountability of the performance of local government agencies. The population of this research is the Regional Work Unit (SKPD) which consists of the Regional Secretariat, DPRD Secretariat, inspectorate, department, agency and Satpol PP. Sample selection used the purposive sampling method. This research uses primary data with data collection methods using questionnaires. The respondents in this research were treasurers in each SKPD of Banyuwangi district. The data analysis technique used is SEM-PLS with the help of SmartPLS 3.0 software for data analysis. The results of this research indicate that the variable implementation of the regional government accounting system and reporting system has a positive effect on the accountability of the performance of regional government agencies. Meanwhile, the variable compliance with statutory regulations has no effect on the accountability of the performance of local government agencies